Disinfection/ammonia removal from aquaculture wastewater and disinfection of irrigation water using electrochemical flow cells: A case study in Hawaii. (14th June 2021) - Qing, Geletu; Foster, Shelby L.; Anari, Zahra; Matlock, Marty; Thoma, Greg; Greenlee, Lauren F.
Abstract: This field case study reports findings on disinfection/ammonia removal from aquaculture wastewater and disinfection of irrigation water carried out at an aquaculture farm and two irrigation locations in Hawaii. We used a flow cell incorporating PtRu/graphite anode and graphite cathode for the disinfection/ammonia removal from aquaculture wastewater, and a flow cell assembled with graphite plates as both anode and cathode for the disinfection of irrigation water. The removal of ammonia followed the indirect oxidation mechanism mediated by free chlorine electro‐generated at the PtRu/graphite anode. Ammonia removal rate increased with the increase in NaCl concentration, applied current density, or flow rate. The disinfection of aquaculture wastewater can be readily achieved due to the presence of highly germicidal free chlorine species. The disinfection of irrigation water was realized without the addition of chemicals. The disinfection mechanism was attributed to the formation of free chlorine from the anodic oxidation of chloride ions naturally occurring in the water sources. The disinfection efficiency decreased with increasing organic matter concentration. In addition to the flow cell approach, we also successfully demonstrated the disinfection of irrigation water by adding electrolyzed NaCl solution or purging with a mixture of air and chlorine gas, both of which were generated on‐site. Practitioner points: Field case study on disinfection/ammonia removal from aquaculture wastewater and disinfection of irrigation water was carried out in Hawaii. Electrochemical flow cell assembled with PtRu/graphite anode and graphite cathode effectively removes ammonia from aquaculture wastewater. Ammonia removal proceeds via the indirect oxidation mechanism mediated by free chlorine electro‐generated at the PtRu/graphite anode. Electrochemical flow cell assembled with commercial graphite electrodes enables fast disinfection of coliform bacteria and E . coli . The primary disinfection mechanism is through chlorine species electro‐generated from chloride oxidation at the graphite anode. Abstract : Field study demonstrates ammonia removal and disinfection using electrochemical flow cells.